‘Sticky Rice’: Variety inertia and groundwater crisis in a technologically progressive state of India - Joshi, Kuhu; Joshi, Pramod Kumar; Khan, Md. Tajuddin; Kishore, Avinash (International Food Policy Research Institute, 2018)
This paper studies the high adoption of Pusa 44, a long-duration and old rice variety cultivated in Punjab, despite the availability of new short-duration varieties and the overall technological advancement of agriculture. We use farm-household data from a primary survey conducted in 2016-17. Pusa 44 yields on average 2.5 quintals higher per hectare than competing short-duration variety PR 121. It also consumes 16 percent additional water because of its longer duration. As energy for groundwater irrigation is provided tariff-free by the state, Pusa 44 farmers obtain higher net returns even though they pump additional groundwater. Consequently, they have little economic incentive to switch to new short-duration varieties. This varietal stickiness is a pressing policy issue considering the ongoing groundwater crisis in the state. We show that Punjab currently incurs an additional energy-subsidy cost of US$ 49 million per annum on irrigating Pusa 44. Future costs will continue to multiply unless farmers are incentivized to switch to short-duration rice varieties.